What Is the Benefit from Publishing a Working Paper in a Journal in Terms of Citations? Evidence from Economics - Klaus Wohlrabe; Constantin Bürgi (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Many papers in economics that are published in peer reviewed journals are initially released in widely circulated working paper series. This raises the question about the benefit of publishing in a peer-reviewed journal in terms of citations. Specifically, we address the question: To what extent does the stamp of approval obtained by publishing in a peer-reviewed journal lead to more subsequent citations for papers that are already available in working paper series? Our data set comprises about 28.000 working papers from four major working paper series in economics. Using panel data methods, we show that the publication in a peer reviewed journal results in around twice the number of yearly citations relative to working papers that never get published in a journal. Our results hold in several robustness checks.
Keywords: A10; A12; 330; peer review; citations; RePEc; working paper; preprint